Analyzing city images. Potentials of the “French School of Discourse Analysis” - Mattissek, Annika (ERDKUNDE, 2010)
Discourse theoretical concepts and poststructuralist approaches have widely been discussed within German human geography in recent years. They argue that language plays a decisive role for the constitution of social realities in general and the formation of power-knowledge structures in particular. However, the question of how these theoretical insights could adequately be implemented in empirical studies has remained a matter of ongoing debate especially as the assumptions underlying the methods of qualitative social research have been criticized by poststructuralist thinkers. This paper draws on writings of the “French School of Discourse Analysis” (Williams 1999) in order to develop a methodical mix of quantitative-statistical and proposition-based techniques that is able to address the meaning effects derived from the formal characteristics of texts. Using a print media analysis of the city image of Leipzig as an empirical example, the potential that this approach has for the depiction of both structural aspects of discourses as well as inconsistencies and conflicts within them is discussed.